VD_FINDINFO Décision / 2013 / 409 vom 8. Mai 2013 - VD Tribunal cantonal (2013)
DÉTENTIONINCARCÉRATION, RISQUE DE FUITE, RISQUE DE COLLUSION, MALADIE | 221 CPP (CH), 227 al. 5 CPP (CH), 227 al. 7 CPP (CH), 396 al. 1 CPP (CH), 90 CPP (CH)